The Effect of Banning Fireworks on Air Quality in a Heavily Polluted City in Northern China During Chinese Spring Festival - Liu, Dexin; Li, Wanlong; Peng, Jianbiao; Ma, Qingxia (Frontiers in Environmental Science, 2022)
Air pollution hinders the development of regional economies, has a negative impact on the ecological environment as well as on the health of people; but what is the impact of fireworks on air pollution and is it necessary on health grounds to ban fireworks during the Chinese Spring Festival? In addressing these questions this paper took advantage of the unique opportunity afforded by Zhengzhou City’s firework prohibition policy of 2016 which effectively banned setting off fireworks during the Spring Festival enabling before and after pollution analyses to carried out. In this paper the Air Quality Index and the concentration levels of the major pollutants PM2.5, PM10, SO2, NO2, CO and O3 throughout the Spring Festival in Zhengzhou City, for seven consecutive years from 2014, were compared and analyzed. The results show that: ① The prohibition of fireworks is of great significance to the improvement of air quality in Zhengzhou. ② It was found that PM10 and PM2.5 were the main pollutants in Zhengzhou during the Spring Festival, and the effect of fireworks on PM10 and PM2.5 concentration levels were more significant compared to those of the gas pollutants. ③ The concentrated discharge of fireworks causes a short-term concentration in air pollution, the levels of which came down in 2016 and most noticeably in 2018 following the strengthening of the policy and the air quality index entered the top 3 grades during the festival. Further analysis in 2020, during the Spring Festival which overlapped with the novel coronavirus outbreak, showed that air pollution associated with the supply of domestic electricity is significant. Therefore, on health grounds it may be necessary but not sufficient to ban fireworks during the Spring Festival as other sources of air pollution need to addressed as well.